The Stuff Games Are Made Of - Barr, Pippin (The MIT Press, 2024)
A deep dive into practical game design through playful philosophy and philosophical play.What are video games made of? And what can that tell us about what they mean? In The Stuff Games Are Made Of,experimental game maker Pippin Barr explores the materials of video game design. Taking the reader on a deep dive into eight case studies of his own games, Barr illuminates the complex nature of video games and video game design, and the possibilities both offer for exploring ideas big and small. Through a variety of engaging and approachable examples, Barr shows how every single aspect of a game—whether it is code, graphics, interface, or even time itself—can be designed with and related to the player experience. Barr's experimental approach, with its emphasis on highly specific elements of games, will leave readers armed with intriguing design philosophy, conceptual rigor, and diverse insights into the inner life of video games. Upon finishing this book, readers will be ready to think deeply about the nature of games, to dive into expressive and experimental game design themselves, or simply to play with a new and expanded mindset.